2010
DOI: 10.1128/jcm.01216-10
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Infections and Colonization by Acinetobacter Genospecies 3

Abstract: Two hundred twenty-one isolates of Acinetobacter baumannii and 15 of Acinetobacter genospecies 3 (AG3) were consecutively collected in a 30-day period during the nationwide project GEIH-Ab2000. Nosocomial acquisition (P ‫؍‬ 0.01), intensive care unit admission (P ‫؍‬ 0.02), and antibiotic pressure (P ‫؍‬ 0.03) were observed to be lower in the AG3 group. AG3 isolates were more frequently implied in wound infections (P ‫؍‬ 0.05), while A. baumannii tended to be recovered from respiratory samples (P ‫؍‬ 0.08). To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…A. pittii and A. nosocomialis are often associated with clinical outbreaks of disease and antibiotic resistance in healthcare institutions [8][9][10]. A. pittii has a high carriage rate on healthy individuals in the community, often at rates higher than A. baumannii [10][11][12]; however, we are unaware of any community-acquired infections being caused by A. pittii. Community-acquired infections caused by A. nosocomialis are rare, though equally as severe as CA-Ab, with only two cases being recently reported in the Northern Territory of Australia [7].…”
Section: Microbiologymentioning
confidence: 99%
“…A. pittii and A. nosocomialis are often associated with clinical outbreaks of disease and antibiotic resistance in healthcare institutions [8][9][10]. A. pittii has a high carriage rate on healthy individuals in the community, often at rates higher than A. baumannii [10][11][12]; however, we are unaware of any community-acquired infections being caused by A. pittii. Community-acquired infections caused by A. nosocomialis are rare, though equally as severe as CA-Ab, with only two cases being recently reported in the Northern Territory of Australia [7].…”
Section: Microbiologymentioning
confidence: 99%
“…With respect to clinical characteristics, A. baumannii has predominantly accounted for nosocomial infection outbreaks in intensive care units (ICU), although A. nosocomialis , A. pittii , and A. ursingii have also caused outbreaks [ 25 26 27 ]. The rates of ICU admissions (15.4% vs. 50.0%), hospital-acquired infections (76.9% vs. 97.2%), and mortality (16.7% vs. 58.6%) were significantly greater in the A. baumannii group than in the non- A. baumannii group [ 9 11 ]. Moreover, Park et al [ 28 ] found that A. baumannii infection was an independent predictor of mortality in patients with Acinetobacter bacteremia, a finding that further emphasizes the importance of correct species identification of Acinetobacter species.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical features and antibiotic susceptibilities of A. baumannii are different from those of non- baumannii Acinetobacter species. A previous study on the clinical characteristics of Acinetobacter infections found that no cases of infection with non- baumannii Acinetobacter species aggravated to severe sepsis or septic shock [ 9 ]. The overall antimicrobial susceptibilities of non- baumannii Acinetobacter species have been much higher than those of A. baumannii .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…baumannii complex (ACB complex), as it is difficult to distinguish them from each other by phenotypic properties (4,12). Like A. baumannii, Acinetobacter genomic species 3 is responsible for both community-acquired and nosocomial infections (2,10). Intensive phylogenetic analysis has led recently to the proposal of Acinetobacter genomic species 3 as a novel species (Acinetobacter pittii) (11).…”
mentioning
confidence: 99%